Analysis of the Level of Religious Moderation of High School Students in Rejang Lebong - Hendra Harmi (Ta'dib: Jurnal Pendidikan Islam, 2022)
The purpose of this quantitative study was to determine the level of religious moderation among students in various high schools in Rejang Lebong Regency. This study involved 536 students (376 girls and 160 boys) from five SMA/SMK in the Rejang Lebong area. The non-test strategy was used to collect data in the form of a questionnaire. A questionnaire containing four markers of religious moderation was used in this study: national attitudes, tolerance, anti-violence, and acceptance of local culture. Based on the findings of the distribution of questionnaires to students in Rejang Lebong Regency, students in Rejang Lebong Regency have a high level of moderation. This can be observed in the percentage statistics given to students for each indication of religion. In addition, in an effort to build student religious moderation, schools in Rejang Lebong Regency also carried out PAI subjects which has been substantially proven to be able to form a moderate Islamic character. Educational institutions can also serve as testing grounds for religious moderation in diverse community settings.